Hibiscus rosa-sinensis L. (red Hibiscus) Tea, Can It Be Used as A Home-Remedy to Control Diabetes and Hypercholesterolemia? - Subhashinie Sanadheera; Deepanjana Subasinghe; Melissa Nethmi Solangaarachchi; Manju Suraweera; Noshara Yushanthi Suraweera; Nadeesha Tharangika (Biology, Medicine, & Natural Product Chemistry, 2021)
According to traditional medicine, Hibiscus is used to treat hypertension, heart diseases and many other ailments. Commercially available Hibiscus tea is prepared with H. sabdariffa and is expensive. H. rosasinensis is the common variety which is abundant in tropical home-gardens, however the scientific data are lacking on the effects. The present review focuses on the available scientific data on the effects of H. rosasinensis on controlling diabetes and hypercholesterolemia. The endeavour was to identify whether H. rosasinensis flower petals as a ‘tea’ is effective for diabetic and hypercholesterolemic patients. Medical databases such as MEDLINE, BMC, BMJ, research gate, Mendelay literature search database, Google scholar and the general engine Google were searched from November 2018 to April 2019. Search was carried out using keywords such as “Hibiscus rosasinensis”, “antidiabetic effects”, “antihyperlipidemic effects”, “toxic effects”, “anti-inflammatory effects”, “phytochemicals in Hibiscus” etc. Data were critically analyzed to assess whether the effective doses of the research studies on a par with the doses present in H. rosasinensis teas. We found thirty-nine journal articles fulfilled the criteria. The data were categorized and extracted on uses of H. rosasinensis, anti-diabetic effects, anti-inflammatory effects, anti-hypercholesterolemic effects and its phytochemicals. The review revealed that the dose of H. rosasinensis petals present in a home-made Hibiscus tea is theoretically sufficient to elicit anti-hyperglycemic and anti-hyperlipidemic effects. Home-made Hibiscus tea is effective in controlling diabetes and hypercholesterolemia without causing acute toxicity.